2008
DOI: 10.1177/0142723707084840
|View full text |Cite
|
Sign up to set email alerts
|

Developmental differences in the effects of negative and positive evidence

Abstract: The current study sought to assess development differences in children's learning of irregular nouns and verbs under conditions of negative and positive evidence. Fifty-five 3-, 4- and 5-year-old children learned nonsense nouns and verbs and were later asked to produce plural forms for the nouns and past tense forms for the verbs. Forms were constructed to be irregular, and half were provided through negative evidence and half through positive evidence. Age, form (noun vs. verb) and evidence type (negative vs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 51 publications
1
35
0
1
Order By: Relevance
“…Children, who are learning language and use speech to express themselves, produce Running head: LANGUAGE DEVELOPMENT AND AIDED COMMUNICATION 25 error forms, unintelligible utterances, and incomplete structures (see Table 1). These immature forms elicit potentially corrective responses from communication partners (Saxton, 2000), offering children opportunities to reflect on their own expressions and to contrast them to more mature forms, (i.e., modified input) to scaffold learning (Strapp, Bleakney, Helmick, & Tonkovich, 2008). If children are not able to produce such immature forms and thereby elicit this kind of negative evidence to guide their construction of a spoken language grammar, they may need explicit learning opportunities to support the development of the syntax-morphology proficiency that peers seem to learn largely implicitly (Weinert, 2009).…”
Section: Access To Conventional Learning Mechanismsmentioning
confidence: 99%
“…Children, who are learning language and use speech to express themselves, produce Running head: LANGUAGE DEVELOPMENT AND AIDED COMMUNICATION 25 error forms, unintelligible utterances, and incomplete structures (see Table 1). These immature forms elicit potentially corrective responses from communication partners (Saxton, 2000), offering children opportunities to reflect on their own expressions and to contrast them to more mature forms, (i.e., modified input) to scaffold learning (Strapp, Bleakney, Helmick, & Tonkovich, 2008). If children are not able to produce such immature forms and thereby elicit this kind of negative evidence to guide their construction of a spoken language grammar, they may need explicit learning opportunities to support the development of the syntax-morphology proficiency that peers seem to learn largely implicitly (Weinert, 2009).…”
Section: Access To Conventional Learning Mechanismsmentioning
confidence: 99%
“…Baker's paradox is also sometimes known as the 'no negative evidence' problem (e.g., Bowerman, 1988;Marcus, 1993), as the assumption is that caregivers do not provide children with evidence regarding the (un)grammaticality of their utterances (e.g., McNeill, 1966). In fact, this is something of a misnomer, as evidence suggests not only that caregivers spontaneously correct such errors, but also that children are sensitive to this feedback (e.g., Chouinard & Clark, 2003;Clark & Bernicot, 2008;Saxton, Backley & Gallaway, 2005;Strapp, Bleakney, Helmick, & Tonkovich, 2008). However, this type of feedback is unlikely to be sufficient as an explanation of the acquisition of restricted generalizations.…”
mentioning
confidence: 99%
“…Despite the fact that parents generally tend to react rather to the content than to the form of a child's pre vious utterance (see Kilani-Schoch et al 2008, Kazakovskaya 2010 both Lithuanian and Russian CDS, and a high index of interrogative production. A number of parental interrogatives are used (similar to natural adult conversation) as requests for information, clarifications of incomprehensible utterances or demonstrations of disagreement, but the majority of the questions appear to be used for a very specific purposes (didactic, supporting language acquisition, e.g., negative evidence, see Hirsh-Pasek et al (1984), Demetras et al (1986), Bohannon, Stanowitz (1988), Farrar (1992), Sokolov, Snow (1994), Saxton (1997Saxton ( , 2000, Saxton et al (1998), Chouinard, Clark (2003), Saxton et al (2005), Strapp et al (2008), Markus (2003)) and in specific forms (e.g., repetitions, reformulations or corrections), which would be inappropriate or redundant in a natural adult conversation (Jefferson 1982, Clark, Wong 2002, Clark, Bernicot 2008. Studies in CDS have identified two maternal conversational styles, directive vs. conversationeliciting, and confirmed that mothers with conversation-eliciting style ask a lot of questions to elicit children's conversational participation and their children have better language abilities (Hoff-Ginsberg 1991, Tulviste, Mizera, De Geer, 2004.…”
Section: Aims Of the Studymentioning
confidence: 99%